Overseas Research: A Practical Guide, 1st edition - Barrett, Christopher B. (Routledge, 2020)
When conducting research in developing countries, an ability to negotiate a bewildering array of cultural and logistical obstacles is essential. Overseas Research: A Practical Guide distills essential lessons from scores of students and scholars who have collected data and done fieldwork abroad, including how to prepare for the field, how and where to find funding for one’s fieldwork, issues of personal safety and security, and myriad logistical and relational issues.